LEGAL DISCOURSE RECONSIDERED: GENRES OF LEGAL TEXTS - BERŪKŠTIENĖ, Donata (Comparative Legilinguistics, 2016)
Being a complex type of discourse, legal discourse is realized through legal texts written in legal language, which are regarded as special-purpose texts different from other kinds of texts in respect of their text-internal and text-external properties. A great variety of legal texts reflects the diversity of law itself. As different legal texts tend to have different functional, structural and linguistic features, they are classified into genres on the basis of different criteria. The analysis of genres of legal texts contributes to the overall understanding and construction of legal discourse in general and legal texts in particular. This paper aims at the overview and discussion of genres of legal texts focusing on specific features of legal texts and criteria of the classification of legal texts into genres.